Students' honesty in evaluating their teachers - Mattar, D. (2014)
Anonymous students’ evaluations to measure teachers’ performance has become extremely popular in universities around the world and are used to make critical decision with respect to faculty personnel retention, promotion and other. One concern for these evaluations is the likelihood for response bias and the degree of reliability. Although exhaustive studies have been published concerning students’ evaluations, yet, few studies have tackled their honesty. Therefore, this paper aims to find out the extent to which students are serious in filling out this evaluation and to identify the factors discouraging them from being honest. During the 2011-2012 academic year, a questionnaire was distributed to 330 students from different faculties, programs, years and GPAs. The results show that the majority (83.9%) of students are serious when filling out the evaluation forms. By order of relevance, students do not fill the evaluation honestly mainly because (i) they think that their opinions will go unnoticed by the dean; (ii) they are bored from filling out forms, (iii) they do not want to harm the instructor. No significant difference in honesty, while evaluating, is found between students with different genders, different programs (graduate vs. undergraduate) and different GPAs. However, when seniority was highlighted, a significant difference appeared: sophomore students show less frankness in filling the evaluations than junior and senior students. Moreover, senior students have the highest tendency of filling out this assessment tool honestly. When the faculty was taken as a basis for comparison, a significant difference appeared between students enrolled in the Faculty of Sciences and students enrolled in the Faculties of Engineering and Business where Sciences students are the least honest. Furthermore, students suggested that an increase in the reliability of their responses could be achieved through face-to-face private discussions with the Dean or the key person in the office.